Understanding Parts of Speech by EFL Students to ease them in constructing an English sentence - Syafitri Ramadhani; Ririn Ovilia (Journal of English Language Teaching, 2022)
Grammar is one important English component that need to be mastered starting from identifying and understanding parts of speech. Parts of speech are English basic component in which words are recognized and classified based on their lexical functions. They consist of eight major parts of speech, such as nouns, pronouns, verbs, adjectives, adverbs, conjunctions, prepositions and interjections. Each part of speech has certain role in composing a sentence. In other words, it is important to be understood by EFL students in order to help them to write a correct sentence. By considering the importance of understanding parts of speech, this study was done to find out how the students’ understanding of parts of speech ease them to construct a sentence. It was a qualitative study. There were 31 students who took Basic grammar class as the participants of this study. The data were collected by English test and interview. The data were analysed narratively to describe how the students’ understanding of parts of speech can ease them to compose a sentence. Based on the result of the research, it can be stated that the students’ understanding of parts of speech could facilitate the students to write a sentence.